Solution of singular one-dimensional Boussinesq equation by using double conformable Laplace decomposition method - Hassan Eltayeb; Imed Bachar; Musa Gad-Allah (Advances in Difference Equations, 2019)
Abstract In this study the method which was obtained from a combination of the conformable fractional double Laplace transform method and the Adomian decomposition method has been successfully applied to solve linear and nonlinear singular conformable fractional Boussinesq equations. Two examples are given to illustrate our method. Furthermore, the results show that the proposed method is effective and is easy to use for certain problems in physics and engineering.